2013
DOI: 10.1016/j.febslet.2013.03.005
|View full text |Cite
|
Sign up to set email alerts
|

Evolutionary conserved motifs constrain the RNA structure organization of picornavirus IRES

Abstract: a b s t r a c tPicornavirus RNAs initiate translation using a 5 0 end-independent mechanism based on internal ribosome entry site (IRES) elements. Despite performing similar functions, IRES elements present in genetically distant RNAs differ in primary sequence, RNA secondary structure and trans-acting factors requirement. The lack of conserved features amongst IRESs represents obstacles for the understanding of the internal initiation process. RNA structure is tightly linked to picornavirus IRES activity, con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
14
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
9
1

Relationship

4
6

Authors

Journals

citations
Cited by 16 publications
(17 citation statements)
references
References 46 publications
3
14
0
Order By: Relevance
“…With regard to the changes induced by different Mg 2+ concentrations on the local RNA flexibility of the apical region of domain 3, it is worth noting that this region harbors three conserved motifs (GNRA, RAAA and the C‐rich loop). Disruption of these motifs or destabilization of the corresponding stems led to a defective IRES and induced changes in the RNA structure of this region . The SHAPE reactivity changes observed upon Mg 2+ increase in the folding buffer are consistent with a strong influence of the divalent cation on the structural organization of this RNA domain.…”
Section: Discussionsupporting
confidence: 57%
“…With regard to the changes induced by different Mg 2+ concentrations on the local RNA flexibility of the apical region of domain 3, it is worth noting that this region harbors three conserved motifs (GNRA, RAAA and the C‐rich loop). Disruption of these motifs or destabilization of the corresponding stems led to a defective IRES and induced changes in the RNA structure of this region . The SHAPE reactivity changes observed upon Mg 2+ increase in the folding buffer are consistent with a strong influence of the divalent cation on the structural organization of this RNA domain.…”
Section: Discussionsupporting
confidence: 57%
“…In support of this hypothesis, a mutational analysis carried out on SL1 residues showed that disruption of the stem reduced IRES activity whereas compensatory mutations restoring the secondary structure recovered translation. 59 Although the nucleotides involved in tertiary interactions remain elusive, our results support the existence of a complex network of long-distant interactions within this IRES region. This hypothesis is in agreement with earlier proposals in which nucleotides belonging to the GNRA motif, the RAAA stem-loop and G 240 within the C-rich bulge are linked in the three-dimensional RNA structure.…”
Section: Discussionsupporting
confidence: 70%
“…The relationship between RNA structure and biological function of types I and II has been analyzed by mutational analysis and RNA probing (Bailey and Tapprich, 2007;Fernandez et al, 2013;Haller and Semler, 1992;Haller et al, 1996;Malnou et al, 2002;Serrano et al, 2009). Additionally, RNA modeling agrees with the experimental observation that mutations disrupting certain stems impaired IRES activity, and conversely, compensatory mutations restored IRES function (Hoffman and Palmenberg, 1996;Martinez-Salas et al, 1996).…”
Section: Picornavirus Ires Elements Diversitymentioning
confidence: 99%